Improvement of Impinging Jet Casing Design On Savonius Turbine Performance - Amron Rosyada; Achmad Baidowi; Sunarsih (International Journal of Marine Engineering Innovation and Research, 2026)
Savonius turbine is one of the various devices used to convert fluid flow energy into electricity. Due to its low efficiency, many studies have been conducted to increase its performance. In this paper, the effect of impinging jet stream direction to concave side of returning blade has been observed. There are 4 casing designs; base casing design (BCD) from previous work and 3 proposed designs which have impinging jet stream direction perpendicularly with the concave side of returning blade azimuth position of 60° (D-I), 75° (D-II), and 90° (D-III) respectively. The study employed two-dimensional CFD (Compu-tational Fluid Dynamic) transient method using Ansys Fluent with Kω-SST (Shear-Stress Transport) as the turbulence model. The result shows that all casing designs are able to rise up the coefficient of power (Cp) of conventional turbine design. Furthermore, D-III and D-II have better performance than BCD at all tip speed ratios (TSRs) while D-I’s Cp curve shows several intersections. D-III surpasses BCD’s peak performance, At TSR =1, by 8%. By applying D-III casing design, the best caseless turbine efficiency (23%) could be improved up to 43% at the same working condition (TSR=0.8). Additionally, the shorter flow passage could increase the impinging jet stream velocity